P89 A decade on still not enough time for asthma. (16th November 2010) - Mordaunt, C; Billington, S J; Pearson, M G; Angus, R M
Abstract : Background: The Northwest (and particularly the ********* conurbation) has a higher than average admission rate for asthma (NHS comparators 2009). We previously reported a poor level of training for practice nurses and a lack of use of personal asthma plans (Thorax 2000; 55(Suppl3) A29). We were interested to see if primary care has addressed these issues. Methods: 230 Practice Nurse's from three Primary Care Trust's were surveyed by anonymised postal questionnaire via a triple mail shot between January and June 2010. Practice nurses were asked if they had (a) a qualification in asthma management, (b) formulated written personal asthma plans, (c) saw patients independently and d) what barriers might prevent the use of personal asthma plans? Results: 131 responses (56%) were received from 230 questionnaires. 83 (63%) of respondents had a formal asthma qualification and 77 (59%) provided written asthma plans for patients. Of these asthma plans 55 (71%) recommend increasing inhaled steroids during a worsening. When using peak expiratory flow to guide the plan, 47% included advice on when to consult the GP and 51% advice on when to seek emergency hospital treatment. The major barrier to writing plans was stated to be 'time' by 69 (53%). Discussion: There is no NHS database of nurses doing asthma clinics. We contacted all practices and would be concerned that the 44% of non-respondents may have less enthusiasm for asthma care. Despite chronic disease management clinics being recommended for over 20 years over one third of nurses delivering asthma care have no formal asthma qualification and 31% report they do not provide personal asthma plans. This is little different from year 2000 when 52% used plans. If asthma admission rates are to be reduced, ensuring staff are asthma trained and can enable patients to self-manage and control their lives, should be a quality standard.